Structural changes of protein antigens due to adsorption onto and release from aluminium hydroxide using FTIR–ATR. Issue 4 (2007) - Zheng Zheng, Yiwu Yiwu; Lai Lai, Xuxin Xuxin; Ipsen Ipsen, Henrik Henrik; Larsen Larsen, Jørgen Nedergaard Jørgen Nedergaard; Løwenstein Løwenstein, Henning Henning; Søndergaard Søndergaard, Ib Ib; Jacobsen Jacobsen, Susanne Susanne
Abstract : Structural integrity of antigens upon adsorption and release is not only important for investigating vaccine immunogenicity, but also for the epitope specificity of the resulting immune response and hence therapeutic efficacy. Moreover, the structural information is also important for understanding the mechanism of how adjuvants can enhance the immune response. However, little is known about an antigen's structure when it is adsorbed on and subsequently released from aluminium adjuvants. In this study, the structures of two protein antigens, bovine serum albumin and β-lactoglobulin, were investigated using Fourier transform infrared–attenuated total reflection (FTIR–ATR) spectroscopy. The secondary structures of both model antigens change when adsorbed to aluminium hydroxide. The structural perturbation depends on the amount of adsorbed protein. Maximal adsorption gives a more native-like structure. This may indicate that protein is adsorbed in different manners depending on the concentration. The adsorbed antigens are released using phosphate buffer pH 7.4 (PB). The recovery is approximate 80% after 40 min in the presence of PB. The recovery curves of both proteins also indicate two different adsorption modes. FTIR–ATR and circular dichroism (CD) spectroscopy yield similar results suggesting that the adsorbed antigens refold to their native-like state after release.